Surviving the grind: how young black women negotiate physical and emotional labor in urban space - McCurn, Alexis S. (Sociological Spectrum, 2020)
This study draws on nearly 2 years of field research in Central East Oakland, CA, to provide an ethnographic account of the daily experiences of poor, young, black women in urban space. Few scholars have explored the collective experiences of young women living in the inner-city and the innovative strategies they develop to navigate daily life in this setting. The accounts from young women in this study reveal the different types of formal and informal labor black women do to ensure survival in the inner-city and how they describe this daily work as the “grind.” The intersection of formal and informal labor that makes up the grind is reflected in three dimensions: the half-time hustle, underground entrepreneurship, and informal support networks. Like men in the neighborhood women must contend with underemployment, poverty and race and class isolation. I explain how black women are impacted in very specific ways by these key structural shifts and harsh structural conditions and must in turn manage constraining and contradictory gendered expectations while negotiating the grind. © 2020, © 2020 Taylor & Francis Group, LLC.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; capitalisme; environnement; intersectionnalité; milieu urbain; projet charge mentale; périodes historiques; racisme; régions géographiques; sexisme; stratégie de survie; systèmes d'oppressions; thématiques; travail; états-unis

L'association des femmes inuites du Nunavik Saturviit : porteuses d'espoir et de paix - Koperqualuk, Lisa Q. (2008)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; environnement; famille; féminisme autochtone; inégalités; maternité; nunavik; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; violences

« Des femmes et de la territorialité » Début d’un dialogue sur la nature sexuée des droits des autochtones - Woudenberg, Gerdine Van; Lapierre, Christine (Recherches amérindiennes au Québec, 2004)
Cet article, qui se situe dans l’ensemble des discours sur les droits des autochtones, explore de façon spécifique le sujet du rapport des femmes à la territorialité. En utilisant comme étude de cas les cultures wabanakies de la côte Est, l’auteure réexamine de manière critique les documents historiques pour analyser le rapport des femmes au « lieu » à travers leur relation à leur environnement et elle étudie comment le contexte de cette relation a été transformé par les processus de colonisation. Puisque ce texte s’insère dans le large champ des discours sur les droits autochtones, il soulève des questions importantes sur la position des femmes autochtones dans les processus actuels de reconnaissance des droits et des titres, non seulement comme participantes actuelles mais aussi comme acteurs historiques.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; environnement; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; territoire; thématiques; wabanakie